Evidence that Lake Cheko is not an impact crater - Collins, G.; Artemieva, N.; Wünnemann, K.; Bland, Phil; Reimold, W.; Koeberl, C. (Blackwell Publishing Ltd, 2008)
In a provocative paper Gasperini et al. (2007) suggest that Lake Cheko, a ~300-m-wide lake situated a few kilometres downrange from the assumed epicentre of the 1908 Tunguska event, is an impact crater. In this response, we present several lines of observational evidence that contradicts the impact hypothesis for the lake s origin: un-crater-like aspects of the lake morphology, the lack of impactor material in and around the lake, and the presence of apparently unaffected mature trees close to the lake. We also show that a tensile strength of 10–40 MPa is required for an asteroid fragment to traverse the Earth’s atmosphere and reach the surface intact and with sufficient velocity to excavate a crater the size of Lake Cheko. Inferred tensile strengths of large stony meteorites during atmospheric disruption are 10–100 times lower. We therefore conclude that Lake Cheko is highly unlikely to be an impact crater.